Marketing of Educational Services in Increasing Customers at Madrasah - Afwanisa, Afradilah; Fidela, Erlinda; Aini, Nurul; Sulaeman, Sulaeman (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study explores the marketing strategies of educational services and their influence on student enrollment at MTs Al-Mukrimin Guppi Bulukasa, an Islamic junior high school in Indonesia. Employing a qualitative descriptive approach, data were collected through observations, interviews with school leaders and teachers, and documentation analysis. The findings highlight a three-stage marketing process comprising planning (community outreach and distribution of promotional materials), organizing (establishment of a school-based marketing team), and implementation (building trust through community engagement). These strategies have proven effective in attracting new students and enhancing the institution’s visibility. The study contributes to the limited literature on educational marketing in Islamic schools by offering practical insights into localized and community-centered approaches. It underscores the importance of strategic planning and relationship-building in improving public perception and institutional growth. The implications of this research are relevant for school leaders seeking sustainable enrollment strategies in increasingly competitive educational environments.